Mechanism of cement paste reinforced by graphene oxide/carbon nanotubes composites with enhanced mechanical properties. Issue 122 (24th November 2015) - Lu, Zeyu; Hou, Dongshuai; Meng, Lingshi; Sun, Guoxing; Lu, Cong; Li, Zongjin
Abstract : This paper presented the enhanced mechanical properties of cement paste reinforced by graphene oxide (GO)/carbon nanotubes (CNTs) composites. The space interlocking mechanism of the GO/CNTs/cement paste composite was proposed. Abstract : This study presents the enhanced mechanical properties of cement paste reinforced by graphene oxide (GO)/carbon nanotubes (CNTs) composites. The UV-vis spectroscopy and optical microscopy results show that the dispersion of CNTs in the GO solution is much better than in an aqueous solution due to the higher electrostatic repulsion, which allows a completely new approach of dispersing CNTs rather than by incorporating a dispersant. More importantly, the GO/CNTs composite plays an important role in improving the compressive and flexural strength of cement paste by 21.13% and 24.21%, which is much higher than cement paste reinforced by CNTs (6.40% and 10.14%) or GO (11.05% and 16.20%). The improved mechanical properties of cement paste are attributed to better dispersed CNTs and enhanced interactions among CNTs by the GO incorporation. Finally, the space interlocking mechanism of the GO/CNTs/cement paste composite with enhanced mechanical properties is proposed.